Insomnia during the COVID-19 pandemic in a Greek population. (July 2020) - Voitsidis, Panteleimon; Gliatas, Ioannis; Bairachtari, Vasiliki; Papadopoulou, Kalliopi; Papageorgiou, Georgios; Parlapani, Eleni; Syngelakis, Markos; Holeva, Vasiliki; Diakogiannis, Ioannis
Highlights: Insomnia prevalence in the Greek population during COVID-19 pandemic was estimated at 37.6%. Women and those living in urban areas are affected more. Loneliness, intolerance to uncertainty, depression, COVID-19 related worry are predictive factors. Abstract: Insomnia is a major health issue associated with great psychological burden. Research of insomnia during a pandemic crisis is limited. The aim of the present study was to explore sleep difficulties during the COVID-19 pandemic in a Greek population. The three-day online survey included questions about sociodemographic characteristics, contact with COVID-19 and COVID-19-related negative attitudes, as well as the Athens Insomnia Scale (AIS), the Intolerance to Uncertainty scale (IUS), the De Jong Gierveld Loneliness scale (JGLS) and the Patient Health Questionnaire-2 (PHQ-2) Depression Scale. Altogether, 2, 427 individuals participated in the study (with 2, 363 of them providing all basic demographic data). Sleep problems were detected in 37.6% of the participants. Women and people in urban areas were more vulnerable to sleep problems, while younger age showed a non-significant trend. Those uncertain about having themselves, or someone close to them contracted the virus, also demonstrated elevated insomnia scores. Lastly, according to the regression analysis, higher levels of intolerance to uncertainty, COVID-19-related worry, loneliness, as well as more severe depressive symptoms, were all predictive of insomnia. Results may be used for the development of therapeutic strategies and implementation of social policies to support people with sleep difficulties.